Proprioceptive Training Effects on Reducing Ankle Injury Risk in Football Players - Nurhayati, Ummy Aisyah; Imron, Moh. Ali; Wiyandari, Niken Tri (Annual Physiotherapy Scientific Meeting Proceeding, 2022)
Introduction : Ankle injury is a common case in soccer players. This condition is due to the ankle as an active facilitator playing an important role in the support of movement when playing. This is one of the factors that can decrease proprioceptive. Proprioceptive is the organism's ability to sense the position and movement of joints. Proprioceptive impairment is caused by ankle injuries such as ankle sprains, ankle strains, ankle dislocations and ankle fractures. The condition of the injury was supported by age, gender, BMI, insufficient warm-up, temperature and humidity, excessive exercise, insufficient rest time and inappropriate exercise facilities. The proprioceptive improvement process needs to be carried out in the form of FIFA 11+ proprioceptive training; this exercise is able to provide an increasing effect on neuromuscular and balance so that these exercises can reduce the risk of ankle injury in soccer players. Methods: The study applied experimental with a quasi-experimental approach to pre- and post-test one grub design treatment, sampling technique using purposive sampling, a sample of 21 people with an exercise program 3x a week for 4 weeks. The research instrument used a modified bass dynamic balance test, and the data analysis used descriptive statistical test, normality test and hypothesis testing. Results: Hypothesis testing using paired sample t-test showed that there was an effect of giving proprioceptive training to reduce the risk of ankle injury in soccer players (P=0.00 P<0.05). Conclusion: There is an effect of giving proprioceptive training to reduce the risk of ankle injury in soccer players.